Explosive resistance training using elastic bands in young female team handball players - Andersen, V.; Steiro Fimland, M.; Toldnes Cumming, K.; Vraalsen, Ø.; Hole Saeterbakken, A. (Sports Medicine International Open, 2018)
The aim of the study was to examine the effects of full-body elastic resistance band training in young female team handball players. 12 players (16.5±0.7 years, 166±5.0?cm, 65.9±8.8?kg) completed an 11-week control period followed by a 9-week elastic resistance band training period. The training program, consisting of 6 exercises, was incorporated into the teams` regular handball training sessions 3 times per week. Each exercise was performed with 3 sets of 6-10 explosive repetitions (5-9 on the Borg CR10 Scale®). The maximal power output in squat and bench press, jump height, throwing velocity and repeated agility run was tested before and after the control and training periods. The elastic resistance band period had greater improvement vs. the control period for countermovement jump with or without arm swing (10% vs. -6 to -2%) and power output at lighter loads (10 to 12% vs. -6 to 0%). For the 3 throwing velocity tests, there were tendencies towards increased velocity in the elastic resistance band period compared to the control period (p=0.07-0.10). For the repeated agility run, there was a reduction in the mean and fastest time compared to the training period (2 to 3% vs. -1 to 1%). In conclusion, a brief, elastic resistance band training program, incorporated into the regular handball training sessions, improved explosive lower-limb performance in young female handball players more than handball training alone.